Venovenous extracorporeal membrane oxygenation in adult respiratory failure: Scores for mortality prediction. Issue 25 (June 2016) - Hsin, Chun-Hsien; Wu, Meng-Yu; Huang, Chung-Chi; Kao, Kuo-Chin; Lin, Pyng-Jing
Abstract : Abstract: Despite a potentially effective therapy for adult respiratory failure, a general agreement on venovenous extracorporeal membrane oxygenation (VV-ECMO) has not been reached among institutions due to its invasiveness and high resource usage. To establish consensus on the timing of intervention, large ECMO organizations have published the respiratory extracorporeal membrane oxygenation survival prediction (RESP) score and the ECMOnet score, which allow users to predict hospital mortality for candidates with their pre-ECMO presentations. This study was aimed to test the predictive powers of these published scores in a medium-sized cohort enrolling adults treated with VV-ECMO for acute respiratory failure, and develop an institutional prediction model under the framework of the 3 scores if a superior predictive power could be achieved. This retrospective study included 107 adults who received VV-ECMO for severe acute respiratory failure (a Pa O2 /FiO2 ratio <70 mm Hg) in a tertiary referral center from 2007 to 2015. Essential demographic and clinical data were collected to calculate the RESP score, the ECMOnet score, and the sequential organ failure assessment (SOFA) score before VV-ECMO. The predictive power of hospital mortality of each score was presented as the area under receiver-operating characteristic curve (AUROC). The multivariate logistic regression was used to develop an institutional prediction model. The surviving to discharge rate was 55% (n = 59). All of the 3 published scores had a real but poor predictive power of hospital mortality in this study. The AUROCs of RESP score, ECMOnet score, and SOFA score were 0.662 ( P = 0.004), 0.616 ( P = 0.04), and 0.667 ( P = 0.003), respectively. An institutional prediction model was established from these score parameters and presented as follows: hospital mortality ( Y ) = −3.173 + 0.208 × (pre-ECMO SOFA score) + 0.148 × (pre-ECMO mechanical ventilation day) + 1.021 × (immunocompromised status). Compared with the 3 scores, the institutional model had a significantly higher AUROC (0.779; P < 0.001). The 3 published scores provide valuable information about the poor prognostic factors for adult respiratory ECMO. Among the score parameters, duration of mechanical ventilation, immunocompromised status, and severity of organ dysfunction may be the most important prognostic factors of VV-ECMO used for adult respiratory failure.